Subjective Identity Concealability and the Consequences of Fearing Identity-Based Judgment. (March 2022) - Le Forestier, Joel M.; Page-Gould, Elizabeth; Lai, Calvin K.; Chasteen, Alison L.
In intergroup contexts, people may fear being judged negatively because of an identity they hold. For some, the prospect of concealment offers an opportunity to attenuate this fear. Therefore, believing an identity is concealable may minimize people's fears of identity-based judgment. Here, we explore the construct of subjective identity concealability: the belief that an identity one holds is concealable from others. Across four pre-registered studies and a set of internal meta-analyses, we develop and validate a scale to measure individual differences in subjective identity concealability and provide evidence that it is associated with lower levels of the psychological costs of fearing judgment in intergroup contexts. Open materials, data, and code for all studies, pre-registrations for Studies 1–4, and online supplementary materials can be found at the following link:https://osf.io/pzcf9/ .